1992
DOI: 10.1007/bf00146375
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic and necrotizing Escherichia coli in human diarrhoea in Spain

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains of serotype 0153: K-:H45 CFA/I+ STa+ were associated with two outbreaks of neonatal diarrhoea that occurred in two different hospitals of Madrid, in one of which several children died. Two other outbreaks were associated with ETEC strains of serotypes 0159: K-:H21 (LT+) and 0159: K-:H4 (LT+ STa+) without CFA/I and CFA/II colonization factors. Necrotizing E. coli (NTEC) strains of serotype 06:K13, producing the cytotoxic necrotizing factor CNF1 and alpha-haemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
12
2
Order By: Relevance
“…Diarrhoeal diseases due to the virulent strains have been extensively reported and account for a substantial degree of morbidity and mortality in different age groups (El-Sheikh and El-Assouli, 2001;Galane and Le Roux, 2001). Virulent strains of E. coli include enteropathogenic E. coli (EPEC), enteroinvasive E. coli (EIEC), enterohaemorrhagic E. coli (EHEC), enteroaggregative E. coli (EAEC), and enterotoxigenic E. coli (ETEC) (Giron et al, 1991;Falbo et al, 1992;Blanco et al, 1992;Chan et al, 1994;Levine, 1987). The clinico-epidemiological patterns of the virulent strains vary, and association with travellers' diarrhoea, extra-intestinal infections, acute, chronic or persistent diarrhoea are known (Falbo et al, 1992;Chan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoeal diseases due to the virulent strains have been extensively reported and account for a substantial degree of morbidity and mortality in different age groups (El-Sheikh and El-Assouli, 2001;Galane and Le Roux, 2001). Virulent strains of E. coli include enteropathogenic E. coli (EPEC), enteroinvasive E. coli (EIEC), enterohaemorrhagic E. coli (EHEC), enteroaggregative E. coli (EAEC), and enterotoxigenic E. coli (ETEC) (Giron et al, 1991;Falbo et al, 1992;Blanco et al, 1992;Chan et al, 1994;Levine, 1987). The clinico-epidemiological patterns of the virulent strains vary, and association with travellers' diarrhoea, extra-intestinal infections, acute, chronic or persistent diarrhoea are known (Falbo et al, 1992;Chan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…NTEC were associated with human extraintesti-nal infections [8][9][10][11][12][13], and isolated from calves with diarrhoea or septicaemia [14][15][16][17]. It has also been suggested that NTEC might be opportunistic pathogens causing diarrhoeal diseases in humans [18][19][20]. However, we have recently found that NTEC strains can be isolated from the faeces of a representative percentage of healthy children and calves; consequently, the association of NTEC strains with human and animal diarrhoea must be carefully investigated (Doctoral thesis of M. Blanco: Entcrotoxigenic, necrotizing and verotoxigenic E.coli of human and bovine origin.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-hemolytic E. coli strains have been associated with human enteric disease, especially among young children (8,(10)(11)(12)(20)(21)(22), and the related enterohemolysin of E. coli O157 (35) appears to be involved in enteric disease. There has, however, been no large prospective case-controlled epidemio-logic study of the association of alpha-hemolysin with human diarrhea.…”
mentioning
confidence: 99%
“…Similar to alpha-hemolysin, the role of CNF1 in diarrhea remains unclear. CNF1-producing strains have been isolated from diarrheal stools and have been associated with several outbreaks in humans (8,10) and animals (13,33,44). Unfortunately, no large, prospective, case-controlled studies have been performed, and the best evidence for the pathogenicity of CNF1-toxigenic isolates is the marked virulence in piglet challenge experiments (45), outlined above.…”
mentioning
confidence: 99%